First report of Euplectromorpha Girault (Hymenoptera: Eulophidae) from Korea, with a key to the genera of Euplectrini in Korea - Jongmin Bae; Sunghoon Jung (Journal of Asia-Pacific Biodiversity, 2023)
Euplectromorpha Girault (Hymenoptera: Eulophidae) is newly recognized from South Korea. We redescribe the newly reported species, E. nigromaculatus (Ashmead) with the images of diagnostic characters. A key to the genera of Euplectrini in Korea and a key to the Palearctic Euplectromorpha species are also provided.